Financial Inclusion and Bank Efficiency in Indonesia - MUTHIA, Fida; RANEO, Agung Putra; ANDAIYANI, Sri (Journal of Advanced Research in Law and Economics, 2020)
The aim of this study is to find out the effect of financial inclusion on bank efficiency in Indonesia. Data from 26 banks for the period of 2011 to 2016 is used to measure bank efficiency using Data Envelopment Analysis (DEA). While the data from the World Bank is used to calculate the ratio of outstanding loans of small and medium enterprises to total outstanding loans in banks to measure financial inclusion index. Panel data regression is done to analyze the effect and the result shows that financial inclusion has a positive and significant effect on bank efficiency where an increase in financial inclusion could improve bank efficiency. The result implies that the government must present a conducive financial environment for the implementation of the SNKI program that can improve financial inclusion and bank efficiency.